Experimental and numerical investigation on residual behavior of high strength reinforced concrete beams subjected to different impact velocities - Dok, Gokhan; Caglar, Naci; Ilki, Alper; Yilmaz, Cemal; Serdar, Ahmet Hamdi (Pergamon-Elsevier Science Ltd, 2026)
This study investigates the dynamic and residual behavior of full-scale high-strength reinforced concrete (RC) beams subjected to low-velocity impact. The aim is to assess both the immediate response under impact and the residual load-carrying capacity after impact, providing a basis for evaluating the post-impact reliability of RC members. Experimental tests were performed by dropping a constant 360 kg mass from heights of 1.5 m, 2.0 m, and 3.0 m, generating distinct impact energies. Beams with different longitudinal reinforcement ratios were designed to represent varying ductility and load-carrying capacities. Dynamic parameters such as impact force, acceleration, displacement, and crack development were measured during impact, while subsequent three-point bending tests evaluated the residual stiffness, strength, and ductility of the impacted beams in comparison with undamaged reference specimens. The results revealed significant reductions in mechanical properties, including stiffness and energy absorption, with a clear tendency for failure modes to shift from flexure to shear under higher impact energies. Residual displacement ductility was substantially diminished, indicating limited serviceability after severe impacts. To complement the experiments, validated finite element models were developed in ABAQUS using a two-step procedure, transferring the damaged state from impact simulations to quasi-static loading. Numerical predictions closely matched experimental findings, with less than 3 % deviation. The combined results highlight the necessity of reassessing the post-impact performance of RC beams and offer practical guidance for improving design provisions against extreme loading conditions.
Keywords: Impact velocity; High-strength concrete; Flexure; Shear; Failure mechanism; Reinforced concrete beam; Residual capacity